Rapid biodegradation of polycyclic aromatic hydrocarbons (PAHs) using effective Cronobacter sakazakii MM045 (KT933253) - Umar, Zubairu Darma; Abd Aziz, Nor Azwady; Zulkifli, Syaizwan Zahmir; Mustafa, Muskhazli (Elsevier, 2017)
Polycyclic Aromatic Hydrocarbons (PAHs) are complex and widely distributed environmental pollutants that can affect living ecosystems. This study was conducted to rapidly degrade phenanthrene and pyrene representing low and high molecular weight of PAHs, respectively. Cronobacter sakazakii MM045 (KT933253) was identified from used engine oil of contaminated soil. PAHs biodegradation was carried out using 2,6-dichlorophenol indophenol (DCPIP) assay. Biodegradation influencing factors including agitation, temperature, pH, inoculums volume and salinity were enhanced using Response Surface Methodology (RSM) by Central Composite Design (CCD). Phenanthrene and pyrene biodegrading metabolites were identified using gas chromatography mass spectrophotometer (GCMS). •Initial biodegradation indicated 75.2% and 54.3% phenanthrene and pyrene degraded by C. sakazakii MM045 within 24 h. After CCD optimisation, 100% degradation was achieved for each of the phenanthrene and pyrene, resulting in the formation of intermediate metabolites.•The identified phenanthrene metabolites were 3,4-dihydroxyphenathrene, phthalic acid, pyruvic acid, acetic acid and oxalic acid. Pyrene intermediates comprised pyrene cis-4,5-dihydrodiol, 3,4-dihydroxyphenanthrene, phthalic acid, pyruvic acid, acetic acid and lactic acid.•Cronbacter sakazakii MM045 was proven to be rapid and effective in degrading PAHs within 24 h despite the unavailability of existing literatures on PAHs biodegradation.